(untitled) (El-Wahat Journal for Research and Studies, 2025)
The Primary School Bears The Responsibility Of Teaching Arabic To Beginners As A Means Of Learning And Communication Skill At The Same Time, So It Adopts The Textual Approach As An Effective Strategy To Present Spoken And Written Texts And Employ Them To Develop The Skill Of Linguistic Communication In All Life Situations, And Works To Link Them With Information And Communication Technology To Keep Pace With Global Civilizational Developments And Invest Them In The Field Of Arabic Language Education. This Study Aims To Show The Effectiveness Of The Spoken And Written Text In Providing The Learner With The Skill Of Linguistic Communication Among Beginners And Exploiting Modern Technological Means To Raise Communicative Situations During The Learning Process. Key Words: Text, Spoken, Written, Communication, Technology